The efficacy of DPP IV inhibitors as adjunct therapy for patients with auto-immune Diabetes: A systematic review and meta-analysis - Laurette Nakhoul; Tracy Nakhoul; Maria Abi Azar; Frederic Harb; Nancy Fawzi Nakhoul (PLoS ONE, 2025)
Rationale Type 1 diabetes mellitus (T1DM) is characterized by autoimmune destruction of pancreatic β-cells, leading to insulin deficiency and hyperglycemia. Although insulin therapy remains the cornerstone of T1DM management, achieving optimal glycemic control remains challenging. Dipeptidyl peptidase-4 (DPP-4) inhibitors, approved for type 2 diabetes, enhance endogenous incretin action and may enhance β-cell function. Some clinical trials have explored their adjunctive use in T1DM. This systematic review and meta-analysis aimed to evaluate the efficacy and safety of DPP-4 inhibitors as an adjunct to insulin in patients with T1DM. Methods We systematically searched PubMed, Cochrane Library, Medline (OVID), Scopus, and ClinicalTrials.gov up to January 2025 for eligible studies. Randomized controlled trials (RCTs) investigating DPP-4 inhibitors versus placebo, both on top of insulin therapy for at least 12 weeks in T1DM patients, were included. The primary outcome was the change in HbA1c. Secondary outcomes included blood glucose, C-peptide, insulin dosage, BMI, weight, adverse events, and HOMA2-β scores. Risk of bias was assessed using the Cochrane RoB 2.0 tool. Data were pooled using a random-effects model, with effect sizes expressed as mean differences (MD) and 95% confidence intervals (CI). Results Out of 1,117 identified studies, seven RCTs comprising 333 participants (176 in the experimental group, 157 in the control group) were included. The addition of DPP-4 inhibitors did not result in a significant or sustained reduction in HbA1c overall, except for a transient improvement between 3 and 6 months (MD −0.10%, 95% CI −0.16 to −0.05, p = 0.0003). DPP-4 inhibitors significantly reduced daily insulin requirements, particularly bolus doses, and postprandial blood glucose (by −34.40 mg/dL), especially in patients with a BMI < 25 kg/m² and diabetes duration <3 years. No significant effects were observed on weight, BMI, fasting blood glucose, fasting or postprandial C-peptide beyond three months. HOMA2-β scores were significantly higher with DPP-4 inhibitors. Safety outcomes were comparable between groups. Conclusions DPP-4 inhibitors appear safe as adjunct therapy to insulin in patients with T1DM. Although they do not offer sustained HbA1c reduction, they may reduce daily insulin requirements, improve postprandial glucose, and transiently enhance β-cell function. Further large-scale studies are needed to better define the subgroups that might benefit from this strategy. Registration This study was registered in PROSPERO (CRD42024610965)